Bridging the Digital Gap: Evaluating Mobile JKN E-Service Quality at Cisaga Health Center - Devi Fitriani; Endah Mustika Ramdani (Innovation Business Management and Accounting Journal, 2025)
The digitalization of public healthcare services in Indonesia, marked by the introduction of the Mobile JKN application, aims to streamline administrative processes and reduce facility congestion. However, a significant "utilization gap" remains prevalent in rural health centers, where technological availability does not always translate into adoption. This study aims to evaluate the digital service quality of the Mobile JKN online queuing feature at the Cisaga Public Health Center (Puskesmas Cisaga) through the lens of the E-Service Quality (E-SERVQUAL) framework. A qualitative descriptive approach was employed, utilizing in-depth interviews, field observations, and documentation. Data were gathered from a diverse group of informants, including BPJS administrative staff and both active and non-active JKN participants, to capture a 360-degree perspective on service delivery. he findings reveal a stark contrast between technological potential and practical reality; despite being a pioneer of digital transformation in Ciamis Regency, nearly 90% of participants still rely on manual queuing systems. Evaluated against the seven E-SERVQUAL dimensions, "Efficiency" emerged as the most significant potential strength for tech-savvy users, whereas "Responsiveness" and "System Availability" were found to be the weakest due to technical disruptions and the absence of integrated on-site support. The study identifies that low digital literacy, inadequate socialization by BPJS Kesehatan, and infrastructural disparities are the primary inhibitors of digital adoption. This study concludes that for digital health transformation to be effective at the grassroots level, it must be supported by a "hybrid" implementation strategy that aligns digital features with local user readiness and technical reliability.